Digital margins: Social and digital exclusion of Gypsy-Travelers in the Netherlands. (June 2016) - Salemink, Koen
Research on digital inclusion increasingly focuses on vulnerable groups, with the prevailing idea that social exclusion leads to digital exclusion. The role of the socio-spatial context is often faded into the background due to user-centric (individual) approaches. This article explores how a vulnerable group, Gypsy-Travelers in the Netherlands, deals with digital developments within their socio-spatial context. Contrary to prevailing theories, the analysis shows that Gypsy-Travelers are digitally engaged, despite their social exclusion. An advantage of the Gypsy-Traveler culture is that extended families on the sites provide a large potential of proxy users for support. Many of the Gypsy-Travelers are digitally engaged, but they engage and participate on their own terms. Furthermore, the digital engagement of Gypsy-Travelers is not a panacea for their social exclusion. In fact, their problematic relation with the settled society is mirrored in online activities. This research shows that digitalization has added a new layer to the interaction between Gypsy-Travelers and settled society. It also demonstrates that more socially and spatially contextualized research approaches can add insights to the debate on social and digital exclusion.